Zaburzenia płynności mówienia – wykorzystanie metody wizualizacji w terapii logopedycznej dziecka jąkającego niepełnosprawnego intelektualnie w stopniu lekkim - Załustowicz, Aleksandra Lidia (Wydawnictwo Naukowe UAM, 2013)
The etiology of this syndrome has many grounds, for example physiological, psychological, lingual and sociological. The main cause of this problem is psychological syndrome. Techniques of visualization have a relaxing effect and help to reduce stress. Therefore, they develop imagination and help our motivation. The aim of this article is to look at visualization and relaxation techniques and how to use them in speech therapy for children with disabilities. The study uses a meta-analysis of publications (research reports, articles, epidemiological and demographic data) on people with the stuttering problem. The study uses analyses and descriptions of patients. This article shows how to use this technique during the speech therapy of children with developmental disabilities. The outcome of the study presented in this paper shows that we should research new ways of working with stuttering children with developmental disabilities. The use of these methods in practice shows that visualization and relaxations could be coupled with the stuttering therapy.
Stuttering – the Use of the Visualization and Relaxation Method in Speech Therapy of Children with Slight Developmental Disabilities
Keywords: stuttering; speech therapy; visualization; relaxation